ปัญหาและลู่ทางการคุ้มครองสิทธิผู้ลี้ภัยเด็กตามกฎหมายระหว่างประเทศ : ศึกษากรณีประเทศไทย - ธนวิศิษฎ์ มหพฤทธิ์ไพศาล (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
According to lnternational law. the protection of a child s rights is widely acknowledged and considered tc) be based on universal rlghts as stated in international documents in the form of Conventions. International custor iary practice, general legal codes accepted by countries as well as courts verdicts are the origins of international law. according to article 38 of the world court s constitution. The child s rights mainly consist of 1) non-discrimination 2 the best Interests of child 3) the right to life, survival and development. and 4) the view s of a child. These rights are n )t to be denled ~n any country. Therefore, even though Thailand does not have any legal obligations regarding the blrth and the protection of the rights of a refugee child, there are other legal Convention on human rights that must be obser ded. These include the protection of the rights of a refugee child to allow himlher to gain the basic rights as statcd in international law. The result of the research proves and concludes that apart from the Convention regarding the refugee cl ild s rights. Thailand abides by other important internati~naal greements on the child s rights. However, there are still . hree challenging notions that may affect the child s rights. They are 1) legal notion 2) physical notion and 3) social nc tion. The Thai government has to pay particular attention to the protection of those notions. As a result, the challenge5 and obstacles of the protection of the rights of a refugee child can be generally caused by the following important fa( tors: 1) legal problem 2) policy problem 3) practical problem 4) attitudes towards refugee problem and 5) knowi ?dge problem. These problems preveni r9fugee children from being treated according to the in basic rights. That also demonstrates that the protection of the rights of a refugee child trial to meet the standards set by international I; IW to be universally upheld. As a consequence, Thailand has to increase measures to cover the rights of a refugee chilc and lo heal ar.3 solve tqe !hree aforementioned challenges. They should be included in the state s policy, and th~l!a w should be correctec 8nd clarified so that Thailand would be able to meet the international standards of the protect 2n oi the rights of a refugee child.